Defect Engineering of Two-Dimensional Transition-Metal Dichalcogenides: Applications, Challenges, and Opportunities - Liang, Qijie; Zhang, Qian; Zhao, Xiaoxu; Liu, Meizhuang; Wee, Andrew T. S (ACS nano, 2021)
Atomic defects, being the most prevalent zero-dimensional topological defects, are ubiquitous in a wide range of 2D transition-metal dichalcogenides (TMDs). They could be intrinsic, formed during the initial sample growth, or created by postprocessing. Despite the majority of TMDs being largely unaffected after losing chalcogen atoms in the outermost layer, a spectrum of properties, including optical, electrical, and chemical properties, can be significantly modulated, and potentially invoke applicable functionalities utilized in many applications. Hence, controlling chalcogen atomic defects provides an alternative avenue for engineering a wide range of physical and chemical properties of 2D TMDs. In this article, we review recent progress on the role of chalcogen atomic defects in engineering 2D TMDs, with a particular focus on device performance improvements. Various approaches for creating chalcogen atomic defects including nonstoichiometric synthesis and postgrowth treatment, together with their characterization and interpretation are systematically overviewed. The tailoring of optical, electrical, and magnetic properties, along with the device performance enhancement in electronic, optoelectronic, chemical sensing, biomedical, and catalytic activity are discussed in detail. Postformation dynamic evolution and repair of chalcogen atomic defects are also introduced. Finally, we offer our perspective on the challenges and opportunities in this field.